Increased Autophagy-Related 5 Gene Expression Is Associated with Collagen Expression in the Airways of Refractory Asthmatics - Poon, Audrey H.; Choy, David F.; Chouiali, Fazila; Ramakrishnan, Rakhee K.; Mahboub, Bassam; Audusseau, Severine; Mogas, Andrea; Harris, Jeffrey M.; Arron, Joseph R.; Laprise, Catherine; Hamid, Qutayba (Frontiers in Immunology, 2017)
Background Fibrosis, particularly excessive collagen deposition, presents a challenge for treating asthmatic individuals. At present, no drugs can remove or reduce excessive collagen in asthmatic airways. Hence, the identification of pathways involved in collagen deposition would help to generate therapeutic targets to interfere with the airway remodelling process. Autophagy, a cellular degradation process, has been shown to be dysregulated in various fibrotic diseases and genetic association studies in independent human populations have identified autophagy related 5 (ATG5) to be associated with asthma pathogenesis. Hence, the dysregulation of autophagy may contribute to fibrosis in asthmatic airways. Objective This study aimed to determine if (1) collagen deposition in asthmatic airways is associated with ATG5 expression and (2) ATG5 protein expression is associated with asthma per se and severity. Methods Gene expression of transforming growth factor beta 1 (TGFB1), various asthma-related collagen types (collagen, type I, alpha 1 (COL1A1); type II, alpha 1 (COL2A1); type III, alpha 1 (COL3A1); type V, alpha 1 (COL5A1), and type V, alpha 2 (COL5A2)), and ATG5 were measured using mRNA isolated from bronchial biopsies of refractory asthmatic subjects and assessed for pairwise associations. Protein expression of ATG5 in the airways was measured and associations were assessed for asthma per se, severity, and lung function. Main Results In refractory asthmatic individuals, gene expression of ATG5 was positively associated with COL5A1 in the airways. No association was detected between ATG5 protein expression and asthma per se, severity, and lung function. Conclusion & Clinical Relevance Positive correlation between the gene expression patterns of ATG5 and COL5A1 suggests that dysregulated autophagy may contribute to sub-epithelial fibrosis in the airways of refractory asthmatic individuals. This finding highlights the therapeutic potential of ATG5 in ameliorating airway remodelling in the difficult-to-treat refractory asthmatic individuals.